Mycobiota and C-Type Lectin Receptors in Cancers: Know thy Neighbors - Zhang, Lilong; Chai, Dongqi; Chen, Chen; Li, Chunlei; Qiu, Zhendong; Kuang, Tianrui; Parveena, Mungur; Dong, Keshuai; Yu, Jia; Deng, Wenhong; Wang, Weixing (Frontiers in Microbiology, 2022)
Numerous studies have demonstrated the importance of gut bacteria in the development of malignancy, while relatively little research has been done on gut mycobiota. As a part of the gut microbiome, the percentage of gut mycobiota is negligible compared to gut bacteria. However, the effect of gut fungi on human health and disease is significant. This review systematically summarizes the research progress on mycobiota, especially gut fungi, in patients with head and neck cancer (HNC), esophageal cancer (EC), gastric cancer (GC), colorectal cancer (CRC), hepatocellular carcinoma (HCC), pancreatic cancer, melanoma, breast cancer, and lung carcinoma-induced cachexia. Moreover, we also describe, for the first time in detail, the role of the fungal recognition receptors, C-type lectin receptors (CLRs) (Dectin-1, Dectin-2, Dectin-3, and Mincle) and their downstream effector caspase recruitment domain-containing protein 9 (CARD9), in tumors to provide a reference for further research on intestinal fungi in the diagnosis and treatment of malignant tumors.